2018
DOI: 10.1097/ico.0000000000001537
|View full text |Cite
|
Sign up to set email alerts
|

An Early Finding of Keratoconus: Increase in Corneal Densitometry

Abstract: The increase in densitometry in the central zone could be useful in detecting subclinical keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
5
39
0
Order By: Relevance
“…In a recent study in our country; It has been stated that with Pentacam Scheimp flug tomography analysis, most, if not all, subclinical keratoconus cases can be detected, and the detection of increased corneal light back distribution may be a more sensitive way to identify keratoconus in its early stages (30). In the same study, it was stated that the increase in densitometry in the central zone could be useful in detecting subclinical keratoconus (30).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent study in our country; It has been stated that with Pentacam Scheimp flug tomography analysis, most, if not all, subclinical keratoconus cases can be detected, and the detection of increased corneal light back distribution may be a more sensitive way to identify keratoconus in its early stages (30). In the same study, it was stated that the increase in densitometry in the central zone could be useful in detecting subclinical keratoconus (30).…”
Section: Discussionmentioning
confidence: 93%
“…The average age was 30.8±11.6 years in the Keratoconus group (22 Female,30 Male) and 32.4±12.4 years in the control group (26 Female,34 Male). The groups were compatible with each other in terms of age and gender (p=0.32, p=0.89, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the patients in the study must be evaluated by using these analyses. The studies by us 4 and Bae et al 5 revealed that even these analyses are not adequate to detect the subclinical keratoconus. We examined the medical records of 3474 patients with keratoconus and 116 (3.3%) cases with subclinical keratoconus were detected.…”
Section: Dear Editormentioning
confidence: 96%
“…To overcome the current screening limitations, Koc and colleagues 12 analyzed the asymptomatic eyes of patients with very asymmetric ectasia ( n = 38) and concluded that densitometric analysis might detect subclinical keratoconus earlier than topographic, topometric, and tomographic analyses. 12 Densitometry is an objective and automatic tool to measure corneal transparency.…”
Section: Introductionmentioning
confidence: 99%